Peer Review Technique in Teaching EFL Writing Skills for Senior High School Students - Jufriadi, Jufriadi; Muin, Fadliyah Rahmah; Mustika, Ria (Faculty of Education and Teacher Training of IAIN Palopo, 2023)
This research aims to determine how peer review improves writing skills for the tenth grade of SMA 13 Luwu Timur. It was applied before the experimental study, focusing on one group pretest and post-test design. The population in this research was the tenth grade of SMA 13 Luwu Timur. The research instrument used was a writing test (pretest and post-test). The data is analyzed by descriptive statistics and calculated using SPSS 22. The data analyzed by calculating the mean score and paired sample t-test revealed that the mean score of students in the post-test (55.08) was higher than the pretest (49.15). The t-count (3,118) is more significant than the t-table (2.179). This shows that the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. It can be said that using peer review in learning can be recommended to improve students' writing skills.